Edukasi dan Pelatihan Deteksi Dini Stroke Metode Fast Pada Lansia di Puskesmas Andalas - Ade Teti Vani; Nadia Dewi; Irwan Triansyah; Dessy Abdullah; Rinita Amelia (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Stroke attacks occur suddenly and unpredictably, so the FAST method is very helpful in reducing the number of pain and death due to stroke. The advantage of the FAST method in early detection is that it can be done independently at various times, with the best time in the morning. Education and training in the form of counseling and workshops are given to the elderly of the Andalas Health Center, which aims to provide knowledge about stroke and train fast method skills so that the elderly can make early detection of stroke. Counseling method using power points and leaflets given to the elderly. When the counseling was carried out, participants were immediately given practical material on the FAST method. The assessment of the scoring workshop is used to see the knowledge and improvement of the skills of the elderly on the material presented. The results of the scoring assessment were obtained by the elderly of the Andalas Health Center to get the skills of the FAST method perfectly.